Counting the Number of Teeth through Panoramic Dental Segmentation - Nur Nafi’iyah ,Febrianti Widyahastuti (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Segmentation (in dentistry) is the separation of tooth and background images as well as the separation of each tooth image. The purpose of segmentation is to facilitate labeling in the recognition of dental patterns. There are many methods of human teeth segmentation (dental radiographs). The most commonly used method is thresholding. In addition to segmentation, another important process is the feature extraction, which is the process of knowing the most important part of the dental image to be processed. In developing a segmentation system of human teeth, based on panoramic dental photos, it takes some very important stages. Accordingly, in this study, there are several stages used, namely: image improvement with CLAHE, thresholding, segmentation of thresholding results using integral projection, and centroid feature extraction. Based on the results found, it is seen that the accuracy of the results of the process of segmentation separation of the teeth with the background using the combined method of thresholding is 66.67%. Meanwhile, the result of the segmentation process of teeth separation has an accuracy of 66.67%. Result count the number teeth of dental panoramic has an accuracy 33.33%.